The Fecal Carriage of Multi-Drug Coliform among Persons Deprived of Liberty in a Certain Correctional Facility in Negros Occidental, Philippines - Jason James P. Lusabia; Nicolette Jaira A. Sitchon; Gia Mykyla Gonzales; Veil Gloreen T. Romero; Ma. Therese O. Cornejo; Stephanie D. Peñaflor; Michaela E. Borromeo; Rovel John P. Montaño; Alain C. Juayang (Rumah Sakit Penyakit Infeksi Prof Dr. Sulianti Saroso, 2026)
Background: The emergence of multidrug-resistant (MDR) Enterobacteriaceae, particularly Escherichia coli and Klebsiella pneumoniae, poses a significant global public health threat. Although these bacteria are common commensals of the human gastrointestinal tract, they may serve as reservoirs of antimicrobial resistance genes that can be transferred to pathogenic strains. Correctional facilities are considered high-risk environments for the transmission of MDR organisms due to overcrowding, limited healthcare access, and close living conditions. This study investigated the fecal carriage of MDR coliforms among persons deprived of liberty (PDLs) in a correctional facility in Negros Occidental, Philippines. Methods: A total of 132 fecal specimens were collected and processed using the modified Landman technique. Isolates were identified through conventional microbiological methods and subjected to antimicrobial susceptibility testing, phenotypic resistance detection, and Multiple Antibiotic Resistance Index (MARI) analysis. Results: Fifty-three coliform isolates were recovered, including 38 E. coli and 15 K. pneumoniae. High rates of resistance were observed to co-amoxiclav and piperacillin/tazobactam, whereas all isolates remained susceptible to carbapenems and amikacin. Four isolates were identified as AmpC producers and three as extended-spectrum β-lactamase (ESBL) producers. The overall MDR prevalence was 7.57%, with E. coli and K. pneumoniae being the predominant MDR organisms. Although the mean MARI was 0.16, ten isolates exhibited MARI values exceeding 0.20, indicating exposure to high-risk antibiotic environments. Conclusion: The presence of MDR coliforms among PDLs highlights correctional facilities as potential reservoirs for antimicrobial resistance. Strengthening antimicrobial stewardship, routine surveillance, infection prevention measures, and policy-driven interventions is essential to limit the emergence and spread of MDR pathogens in correctional settings.